Synthesis and in vitro evaluation of [18F]FECIMBI-36: A potential agonist PET ligand for 5-HT2A/2C receptors. Issue 18 (15th September 2015) - Prabhakaran, Jaya; Underwood, Mark D.; Kumar, J.S. Dileep; Simpson, Norman R.; Kassir, Suham A.; Bakalian, Mihran J.; Mann, J. John; Arango, Victoria
Graphical abstract: Abstract: Radiosynthesis and in vitro evaluation of [ 18 F]-2-(4-bromo-2, 5-dimethoxyphenyl)- N -(2-(2-fluoroethoxy)benzyl)ethanamine, ([ 18 F]FECIMBI-36) or ([ 18 F]1 ), a potential agonist PET imaging agent for 5-HT2A/2C receptors is described. Syntheses of reference standard1 and the corresponding des-fluoroethyl radiolabeling precursor (2 ) were achieved with 75% and 65% yields, respectively. In vitro pharmacology assay of FECIMBI-36 by [ 3 H]-ketanserin competition binding assay obtained from NIMH-PDSP showed high affinities to 5-HT2A R ( K i  = 1 nM) and 5-HT2C R ( K i  = 1.7 nM). Radiolabeling of FECIMBI-36 was achieved from the boc-protected precursor2 using [ 18 F]-fluoroethyltosylate in presence of Cs2 CO3 in DMSO followed by removal of the protective group. [ 18 F]1 was isolated using RP-HPLC in 25 ± 5% yield, purity> 95% and specific activity 1–2 Ci/μmol ( N  = 6). In vitro autoradiography studies demonstrate that [ 18 F]1 selectively label 5-HT2A and 5-HT2C receptors in slide-mounted sections of postmortem human brain using phosphor imaging. Our results indicate the potential of [ 18 F]1 for imaging 5-HT2A/2C receptors in the high affinity state in vivo using PET imaging.